2020
DOI: 10.1002/jcop.22396
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of safety and subjective well‐being of Brazilian children

Abstract: Safety is considered an important aspect of life and well-being. However, few studies have examined the relationship between safety and well-being among children, especially in Latin American.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 20 publications
0
4
0
3
Order By: Relevance
“…Likewise, the community involvement represents a potential benefit for emancipated foster youth; some studies (e.g., Magson et al, 2016) highlight that the feeling of belonging to the community could decrease risk-taking behaviors among disadvantaged emerging adults. Sarriera and Bedin (2015) developed a socio-community well-being model, including variables related to the feeling of belonging to the community in the idea of well-being. Therefore, an increase in relational satisfaction in life requires interpersonal and collective spheres to be more integrated (Prillelstensky, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the community involvement represents a potential benefit for emancipated foster youth; some studies (e.g., Magson et al, 2016) highlight that the feeling of belonging to the community could decrease risk-taking behaviors among disadvantaged emerging adults. Sarriera and Bedin (2015) developed a socio-community well-being model, including variables related to the feeling of belonging to the community in the idea of well-being. Therefore, an increase in relational satisfaction in life requires interpersonal and collective spheres to be more integrated (Prillelstensky, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies could include gender as a variable of interest when analyzing cross-nationally the relationships between satisfaction with safety and how adults listen to children and take what they say into account and children's SWB, since some differences have been detected previously for safety perceptions, generally in favor of boys (see, for instance, Sarriera et al, 2020). They could also be contrasted with objective indicators in line with the work of Uyar-Semerci et al (2017) who observed that differences in safety perceptions by gender are influenced by the "safety welfare context for children", i.e., objective conditions regarding the provision of health, education, and more at the country level, with girls showing lower SWB in low safety contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Satisfaction with safety (Ben-Arieh & Shimoni, 2014;González et al, 2012;González-Carrasco et al, 2018;Lee & Yoo, 2015;Rees, 2019;Sarriera et al, 2020;Steckermeier, 2019;Varela et al, 2020) and satisfaction with how adults listen to children and take what they say into account (Corominas et al, 2020;Kutsar et al, 2019;Rees & Main, 2015) are two variables that have been shown to contribute greatly to children's subjective well-being (SWB) in many countries. However, little is known about the relationships between satisfaction with safety and satisfaction with how adults listen to children and take what they say into account, and what contributes to these two satisfaction variables themselves, specially the latter one.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these findings prompt schools to reassess their strategies to address the potential impacts arising from these challenges (Conrad et al, 2022;Fonte & Osti, 2020). Research also underscores the consequences of failing to identify, evaluate, and intervene early, which can contribute to a cycle of exclusion manifested as school dropout, behavioral issues, underemployment, and limited access to further educational opportunities (Coacci et al, 2023;Sarriera et al, 2021).…”
Section: Introductionmentioning
confidence: 99%